2005
DOI: 10.1177/0163278704273084
|View full text |Cite
|
Sign up to set email alerts
|

Can Physicians Improve Patient Satisfaction with Long Waiting Times?

Abstract: The purpose of our study was to determine how time spent with the physician might be related to patient dissatisfaction with their waiting time. During a 2-month period, patients in our internal medicine resident continuity clinic completed a survey assessing their satisfaction with their waiting time and their estimates of their waiting time and time spent with the resident physician. For patients with long waiting times (more than 15 min in the waiting room or more than 10 min in the exam room), patient diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 22 publications
6
38
3
Order By: Relevance
“…b Other is defined as the whole team, primary care physician, or consultants. (12) 100 (8) 94 (16) My physician spent enough time with me 95 (57) 94 (16) 88 (7) 76 (13) My physician dresses professionally 97 (58) 100 (17) 100 (8) 100 (17) My physician treated me with respect 100 (60) 100 (17) 100 (8) 100 (17) My physician communicated at a level I could understand 97 (58) 94 (16) 100 (8) 100 (17) I would want this physician to treat me again 98 (59) 100 (17) 100 (8) 100 (17) a Intern is defined as subintern medical students + postgraduate year 1 residents. b Other is defined the whole team, primary care physician, or consultants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…b Other is defined as the whole team, primary care physician, or consultants. (12) 100 (8) 94 (16) My physician spent enough time with me 95 (57) 94 (16) 88 (7) 76 (13) My physician dresses professionally 97 (58) 100 (17) 100 (8) 100 (17) My physician treated me with respect 100 (60) 100 (17) 100 (8) 100 (17) My physician communicated at a level I could understand 97 (58) 94 (16) 100 (8) 100 (17) I would want this physician to treat me again 98 (59) 100 (17) 100 (8) 100 (17) a Intern is defined as subintern medical students + postgraduate year 1 residents. b Other is defined the whole team, primary care physician, or consultants.…”
Section: Resultsmentioning
confidence: 99%
“…15 A study conducted in an outpatient ophthalmology clinic showed that a simple handshake and introduction improved satisfaction, 16 and another found that by decreasing waiting times and by spending more time with a patient, satisfaction was improved. 17 Although a number of studies in the outpatient setting have assessed the variables that affect patient satisfaction, there are fewer studies related to inpatient care by resident physicians. 3,4,10,[14][15][16][17] Some of these have found that a…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions that patients have with staff, volunteers and providers has been identified as a factor in patient satisfaction in previous studies, especially in regards to phone calls and wait times, though the actual waiting time is not longer than that at other regular clinic in the same geographical area [12,17]. Since the clinic is run mostly by volunteers who do not always feel that they receive proper training, the attitudes of some receptionists which were negatively perceived may be due to the fact that they had multiple tasks at the front desk.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients admitted during off-hours more frequently encounter delays in undergoing catheterization for MIs, leading to higher mortality (28). Long wait times may be associated with decreased overall satisfaction with treatment (29,30), though other research has found that patient perceptions of time are often inaccurate, with over-more than under-estimations of wait times to see physicians (31). Indeed, perceptions rather than actual wait times may predict patient satisfaction (32).…”
Section: Introductionmentioning
confidence: 99%